Scale Development Study to Determine the Effectiveness of Digital Transformation in Businesses: An Application in Turkish Defence Industry - Sürmen, Yunus Emre; İrak, Gülay; Bılır, Kadrıye Burcu Ongen (My University, 2024)
The global attractiveness of digital transformation technologies leads many nations to increase their investments in these technologies and to achieve a stronger economic position. While this process can be considered in the context of many sectors, it has emerged more clearly in recent years, especially in the defence industry. Not only in many developed countries but also in Turkey, especially with the developments in the last 15 years, the defence industry sector can find a place among the notable countries in the world. Therefore, the use of these technologies can be expressed as a dynamic structure whose potential increases daily thanks to the added value it creates and the ecosystem it has created. However, this process is not only the application field of the private sector but also creates value in the context of the theoretical framework and concepts revealed by scientific studies. This study, it is aimed to develop a scale to determine the ‘digital transformation effectiveness’ in defence industry enterprises. In this framework, the scale and questionnaire questions were sent to companies operating in the Turkish defence industry, and 65 companies responded. The data was subjected to validity and reliability analyses using SPSS 26 and AMOS 26 programs, followed by statistical testing through exploratory factor analysis and confirmatory factor analysis. The findings showed that the scale has sufficiently high internal consistency, has explanatory and confirmatory factor validity, and also has criterion validity based on sub-dimensions.
Keywords: Digital Transformation; Defence Industry; Digital Transformation Effectiveness Scale